2016
DOI: 10.1111/and.12553
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of paracetamol-induced reproductive damage by chrysin in male rats via reducing oxidative stress

Abstract: Paracetamol (PRC) is a nonsteroidal anti-inflammatory drug used widely as a painkiller for various diseases and as the symptomatic flu cure in several countries worldwide. PRC toxicity may occur under conditions of the overdose usage. Chrysin (CR) is a flavonoid that is naturally present in several plants, honey and propolis. The aim of this study was to investigate the effects of CR (at the doses of 25 mg kg and 50 mg kg ) pre-treatment over seven consecutive days against PRC-induced reproductive toxicity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 39 publications
3
47
1
Order By: Relevance
“…Whereas in overdose, PRC can be detrimental to various tissues [20,[33][34] . High dose PRC transform into NAPQI (N-Acetyl-p-benzoquinone imine) -toxic metabolite by cytochrome p450 enzymes in the biological systems.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Whereas in overdose, PRC can be detrimental to various tissues [20,[33][34] . High dose PRC transform into NAPQI (N-Acetyl-p-benzoquinone imine) -toxic metabolite by cytochrome p450 enzymes in the biological systems.…”
Section: Discussionmentioning
confidence: 99%
“…In PRC induced hepatotoxicity studies when toxication group in comparison with control group, it was observed significant increase in MDA level (P<0.05) in rats [39,40] . Aksu et al [20] determined that the decreasing of GSH-px and SOD activity of testicular tissue in the PRC group when compared to the control group in rats. In present study, it is thought that the increasing in MDA level, the decreasing in GSH level, CAT, SOD and GPx activities arise from the harmful effect of PRC via NAPQI pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To estimate the sperm motility, randomly selected three different fields from each sample were evaluated. The average of three field estimations was calculated as the final motility score of the sample [15,16] .…”
Section: Semen Evaluationmentioning
confidence: 99%